2018
DOI: 10.3126/acclm.v3i2.20739
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of Uterine Leiomyoma in Hysterectomy Specimens

Abstract: BACKGROUNDUterine leiomyoma is the most common benign neoplasm in women of reproductive age group. Hysterectomy is a mode of therapy in uterine Leiomyoma. The objective of this study was to evaluate the histopathological changes in hysterectomy specimens with uterine leiomyomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
2
11
1
Order By: Relevance
“…Single leiomyoma was seen in (73.6%) and multiple in (26.4%).Multiple leiomyomas when present were most common in intramural and subserosal location (35.7%). Similarly Bhatta et al [13] showed single leiomyoma in (80.95%) and multiple in (19.05%).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Single leiomyoma was seen in (73.6%) and multiple in (26.4%).Multiple leiomyomas when present were most common in intramural and subserosal location (35.7%). Similarly Bhatta et al [13] showed single leiomyoma in (80.95%) and multiple in (19.05%).…”
Section: Discussionmentioning
confidence: 76%
“…Various degenerative changes seen in leiomyoma were hyaline degeneration (51.5%), then red degeneration in (21.2%) and both seen in (9.1%), cystic degeneration and calcification seen in (6.1%), fatty change and myxoid degeneration seen in (3%). Bhatta et al [13] showed hyaline degeneration whichoccurred most frequently (7.14%), followed by calcification in (1.78%), myxoid degeneration in (1.2 %), hydropic degeneration in (0.6%) cases. Cut section morphology showed that most of them were unremarkable in (42%), single fibroid present in (39%), multiple fibroid in (14%), cervical polyp in (4% ) and (1% ) was atrophic.…”
Section: Discussionmentioning
confidence: 98%
“…The spectrum of benign diseases in hysterectomy specimens include uterine leiomyomas, adenomyosis, endometrial polyps, endometrial hyperplasia, endometritis, disordered proliferative phase endometrium and endometrial stromal nodule. 4,5,6,7 Out of which most frequent pathology encountered is leiomyoma. 3,5,8,9,10 Uterine leiomyoma is defined as benign tumor of smooth muscle origin.…”
Section: Resultsmentioning
confidence: 99%
“…4,5,6,7 Out of which most frequent pathology encountered is leiomyoma. 3,5,8,9,10 Uterine leiomyoma is defined as benign tumor of smooth muscle origin. Incidence of leiomyoma is found to be different according to different studies and it ranges from 20.5-69%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation